Assistance For Strengthening Farmer Group Leadership 3G-AGO Village Todo, Satar Mese North District Manggarai-Nusa Tenggara Timur - Lena Ellitan (Joong-Ki : Jurnal Pengabdian Masyarakat, 2022)
One of the efforts that can be done is through community empowerment in agriculture, especially the horticultural agriculture sub-sector so that people can get out of this multidimensional crisis. If we look at the geographical conditions and the life of the people in Manggarai, especially in Ago Village, Todo Village, North Satarmese Subdistrict, which is agrarian, the development in the agricultural sector is very suitable to be implemented and also to support empowerment efforts carried out by the government. Therefore, farmers who are members of the 3G Farmer Group at Kampung Ago are trying to improve their Horticultural farming business in order to improve mutual welfare through the development of Organic Agriculture on our lands. Basically the group still has limitations in both Knowledge and Business Capital. Activities This community service activity was attended by leaders and members of the 3G-AGO farmer group who are practicing to develop farmer group organizations. They consist of 20 members who have officially joined this farmer group and 4 administrators. The activity will be held on Saturday 5 March 2022 and Sunday 6 March 2019 starting at 09.00 WIB until 12.00 WIB through zoom online. The participants were quite enthusiastic about participating in this training activity. At first, participants were given material according to the theme of this service. The material presented was enough to open their horizons about the importance of organizational governance and leadership. The provision of material is not only given in a lecture model, but is combined with several other methods to make it more relevant. Participants are invited to actively participate in the training process, by developing their creativity to discuss leadership and organizational issues, especially in the era of the industrial revolution 4.0. The highest effectiveness value on membership insight is due to the efforts of members who are often present and active in activities made by farmer groups so that the longer the membership period of farmer group members, coupled with a strong desire to learn and actively participate in membership activities will produce knowledge insights. and also experience in organization. All of this really requires strengthening leadership in the 3G-AGO Farmer Group, Todo Village, North Satar Mese District, Manggarai – East Nusa Tenggara.